2018
DOI: 10.5539/elt.v11n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reading Skills and Translation Ability of Thai EFL Students: Pragmatic, Syntactic, and Semantic Aspects

Abstract: Translation ability requires many language skills to produce an accurate and complete text; however, one important skill, critical reading in the research, has been neglected. This research, therefore, employed the explanatory sequential mixed method to investigate the differences in Thai-English translation ability between students with a high level of critical reading skill and students with a low level of critical reading skill, and to examine the relationship between translation ability and critical readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…This study further revealed that by engaging in translation activities in reading classes, the experimental group significantly outperformed the control group (which had a higher mean score on the pre-test even though the difference was not statistically significant) after being exposed to the intervention for eight weeks in sixteen classes. Furthermore, this study was in line with the results of Sakurai (2015), Lee, Schallert, and Kim (2015), Sriwantaneeyakul (2018) who had suggested that translation could offer a boost in the performance levels of EFL learners in reading comprehension. Also, the results were in parallel with Lee (2013), who had found that the learners in the experimental group who had practiced translation in their reading classes outperformed the control group both in translation tasks and tasks that inquired other aspects of reading comprehension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study further revealed that by engaging in translation activities in reading classes, the experimental group significantly outperformed the control group (which had a higher mean score on the pre-test even though the difference was not statistically significant) after being exposed to the intervention for eight weeks in sixteen classes. Furthermore, this study was in line with the results of Sakurai (2015), Lee, Schallert, and Kim (2015), Sriwantaneeyakul (2018) who had suggested that translation could offer a boost in the performance levels of EFL learners in reading comprehension. Also, the results were in parallel with Lee (2013), who had found that the learners in the experimental group who had practiced translation in their reading classes outperformed the control group both in translation tasks and tasks that inquired other aspects of reading comprehension.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the relevant literature also shows that engaging in intensive and extensive reading skills also support students' translation skills, which, in turn, further reinforces their reading skills. For example, Sriwantaneeyakul (2018) carried out a mixed methods study to reveal the relationship between translation ability and students' critical reading skills by testing the translations made by students with superior critical reading skills and those with lower critical reading skills. The study revealed a statistically significant difference between accuracy of Arab World English Journal www.awej.org ISSN: 2229-9327 428 translation made by the two groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results discussed so far demonstrate the importance of critical thinking for translators and point to the need for the inclusion of critical thinking skills as a learning outcome in T&I departments' curricula, as is also supported in the relevant literature (Kashirina, 2015;Moghaddas and Khoshsaligheh, 2019;Çetiner, 2018;Sriwantaneeyakul, 2018;Mohseni and Satariyan, 2011). Critical thinking can be taught and learned (Halpern, 1999, p. 70).…”
Section: Discussionsupporting
confidence: 60%
“…In a very recent research, Sriwantaneeyakul (2018) embarked on an explanatory sequential mixed method study on the critical reading skills and translation ability. For this study, they selected randomly 60 English major students from a Thai university.…”
Section: Past Studies On Reading Comprehension and Translationmentioning
confidence: 99%